Analisa Atas Pelaksanaan Audit Mutu Internal Untuk Mengevaluasi Efektifitas Penerapan Sistem Manajemen Mutu ISO 9001:2000 Studi Kasus Pada PT. Murni Cahaya Pratama - Hastoni, Hastoni (STIE Kesatuan, 2010)
Internal quality audit is a very important activity. Itâs a must in ISO 9001:2000 standard implementation to observe quality by making verification of the suitability and effectiveness of quality system application towards reference standard and the policies determined. Internal quality audit is a process appraisal and a system to see whether the process and system are in line with procedure ducumented and to see the effectiveness of the procedure. By doing this appraisal, the company will be able to know the condition and siuation at this time. Finally, the results of this audit will be used as an instrument in carrying out improvement and prevention action. Therefore, international standard emphasizes the importance of audit as means of monitoring and verifying. ISO 9001 : 2000 is an international standard for quality management system. ISO 9001 : 2000 determines requirements and recommendation for design and evaluation of quality management system which has a goal to ensure that an organization will provides products which comply with the requirements determined. ISO 9001 : 2000 is only quality management system standard and it is not products standard. However, itâs expected that the products yileldedfrom international quality management system will be able to yield products having appropriate standard quality. The implementation of internal quality audit at PT Murni Cahaya Pratama shows that the internal quality audit has been in accordance with the plan and procedure. The results of internal quality audit are used for improving either the system or products. The quality management system of ISO 9001 : 2000 applied at PT Murni Cahaya Pratama has been effective and efficient enough. However, there are several facts indicating the inefficiency and ineffectiveness could be. It can be viewed from the irrelevance based on the findings of audit, that is the causal factors of the inefficiency and ineffectiveness are human error and lack of knowledge and comprehension concerning the importance of documentation, especially performed by new employees. The authorâs advice on the results of internal quality audit that has been done at PT Murni Cahaya Pratama is ISO 9001 : 2000 and internal quality auditor training should be carried out. Thereby, all employees understand the importance of implementing procedure and documentation well and it can improve auditorâs ability in auditing process. Itâs included setting procedure in returning goods from customers so that when technical service personnel brings the returned goods to werehouse, it can work well in accordance with the procedure. In addition, it must be consistent in making evaluation to suppliers and in maintaining the results of assessment records.